2014
DOI: 10.1007/s00018-014-1713-1
|View full text |Cite
|
Sign up to set email alerts
|

A potential pathophysiological role for galectins and the renin–angiotensin system in preeclampsia

Abstract: This review discusses a potential role of galectins and the renin-angiotensin system (RAS) in the pathophysiology of preeclampsia (PE). Preeclampsia affects between 3 and 5 % of all pregnancies and is a heterogeneous disease, which may be caused by multiple factors. The only cure is the delivery of the placenta, which may result in a premature delivery and baby. Probably due to its heterogeneity, PE studies in human have hitherto only led to the identification of a limited number of factors involved in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…Thus, the eCTB subpopulation might play a role in the dysregulation of the renin-angiotensin system that is observed in preeclampsia. 73 This category of differential expression genes also included CHI3L1 (a glycosidase that is an important modulator of the tumor microenvironment), 74 VTRNA2-1 (which plays important roles in apoptosis), 75 HMOX1, and KDR (VEGFR-2), which we previously showed was down-regulated as cytotrophoblasts differentiate along the invasive pathway. 30 Its up-regulation in the context of sPE is consistent with deficits in eCTB differentiation.…”
Section: Gsta3mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the eCTB subpopulation might play a role in the dysregulation of the renin-angiotensin system that is observed in preeclampsia. 73 This category of differential expression genes also included CHI3L1 (a glycosidase that is an important modulator of the tumor microenvironment), 74 VTRNA2-1 (which plays important roles in apoptosis), 75 HMOX1, and KDR (VEGFR-2), which we previously showed was down-regulated as cytotrophoblasts differentiate along the invasive pathway. 30 Its up-regulation in the context of sPE is consistent with deficits in eCTB differentiation.…”
Section: Gsta3mentioning
confidence: 99%
“…A great deal of work over many decades has gone into investigating the role of the circulating reninangiotensin system in preeclampsia. 73 The renin-angiotensin system, which plays a major role in regulating blood pressure, 104 is dysregulated in hypertension. Patients with preeclampsia have lower plasma renin levels 105,106 and higher sensitivity to angiotensin II, 107,108 which predates the appearance of the signs of this pregnancy complication.…”
Section: Research Implicationsmentioning
confidence: 99%
“…In 2005, Redman proposed two stages of preeclampsia [9] and that model has persisted with modifications to guide our understanding of the disorder [10, 11]. In Stage 1 of preeclampsia (pre-clinical) which occurs in the first half of pregnancy, defective placentation occurs resulting in placental ischemia and release of placental factors into the maternal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cross-sectional study showed that urinary angiotensinogen/creatinine ratio was correlated with high blood pressure and proteinuria in preeclampsia ( Yilmaz et al, 2015 ). The renin-angiotensin system has also been implicated in the pathogenesis of preeclampsia ( Verdonk et al, 2014 ; Blois et al, 2015 ). However, the results of investigations on the significance of the renin-angiotensin system in gestational diabetes and preeclampsia have been contentious ( Gathiram and Moodley, 2020 ).…”
Section: Introductionmentioning
confidence: 99%